LIPG is a novel prognostic biomarker and correlated with immune infiltrates in lung adenocarcinoma. Issue 1 (26th December 2022) - Wang, Shan; Chen, Zhaoxin; Lv, Hongwei; wang, Cong; Wei, Huamin; Yu, Jing
Abstract: Background: Although many biomarkers for lung adenocarcinoma (LUAD) have been identified, their specificity and sensitivity remain unsatisfactory. Endothelial lipase gene ( LIPG ) plays an important role in a variety of cancers, but its role in lung adenocarcinoma remains unclear. Methods: TCGA, GEO, K‐M plotter, CIBERSORT, GSEA, HPA, and GDSC were used to analyze LIPG in LUAD. Data analysis was mainly achieved by R 4.0.3. Results: The expression of LIPG in LUAD tissues was higher than that in adjacent normal tissues, especially in women, patients aged >65 years, and those with lymph node metastasis. High expression predicted a poor prognosis. The results of enrichment analysis suggest that LIPG may exert profound effects on the development of LUAD through multiple stages of lipid metabolism and immune system regulation. In addition, LIPG expression was significantly correlated with the expression levels of multiple immune checkpoint genes and the abundance of multiple immune infiltrates, including the activated memory CD4 T cell, M1 macrophage, neutrophil, plasma cells, and T follicular helper (Tfh) cells in the LUAD microenvironment content. At the same time, patients with high LIPG expression respond well to a variety of antitumor drugs and have a low rate of drug resistance. Conclusions: LIPG is a prognostic marker and is associated with lipid metabolism and immune infiltration in LUAD. Abstract : Relationship between LIPG gene expression and overall survival (OS), disease‐free survival (DFS), and progression‐free survival (PFS) in patients with LUAD.